Lean Six Sigma yellow belt - Vanzant Stern, Terra; Pezet, Don (Packt Publishing, 2024)
The course begins with an introduction to Lean Six Sigma (LSS), unraveling its history and foundational concepts. It delves into identifying waste and defects, crucial in process improvement. The journey through the course includes a comprehensive look at project management techniques and the Plan-Do-Check-Act cycle, essential in LSS implementation. The course focuses on the five phases of LSS: Define, Measure, Analyze, Improve, and Control. Each phase is explored in depth, with multiple parts ensuring a thorough understanding. You'll learn about defining project goals, measuring process performance, analyzing data for insights, implementing improvements, and controlling future process performance. The course wraps up with strategic insights into achieving buy-in for LSS initiatives and preparing for the next steps in your LSS journey. By the end of the course, you'll have a holistic understanding of how LSS can drive significant improvements in any organization. What you will learn Identify and eliminate process waste Learn the Plan-Do-Check-Act cycle Control and sustain process gains Gain skills for securing project buy-in Explore LSS project management essentials Utilize tools for effective data analysis Audience This course is ideal for professionals seeking to improve process efficiency and quality. A basic understanding of business processes is beneficial. This course is perfect for those looking to align their skills with Lean Six Sigma methodologies and enhance their problem-solving abilities. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Terra Vanzant Stern, Phd: Dr Stern is a Six Sigma Master Black Belt and the principal of SSD Global Solutions, Inc. She has written several books and articles on problem solving, process improvement and leadership. Her most recent book, Lean and Agile Project Management was released as a second edition in May 2020. Don Pezet: Don Pezet, with over 25 years in IT, brings rich experience from his time as a field engineer in finance and insurance, supporting networks globally. A Linux enthusiast, he's skilled in Red Hat and Ubuntu, and has a long-standing connection with macOS and Apple products since the mid-90s. For the last 15 years, Don has dedicated himself to IT education, co-founding ITProTV in 2012 to provide top-tier IT training. As ACI Learning's CPO, he continues to deliver innovative training to IT professionals. His credentials include Microsoft MCSE, Amazon ACSA, Cisco CCNP, LPI LPIC-2, PMI PMP, and several CompTIA certifications like A+, Network+, Security+, and Linux+.
Online resource; title from title details screen (O'Reilly, viewed January 23, 2024)
Keywords: Six sigma (Quality control standard); Organizational effectiveness; Lean manufacturing; Six Sigma; Efficacité organisationnelle; Production allégée; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet